Semiempirical UNO–CAS and UNO–CI: Method and Applications in Nanoelectronics - Dral, Pavlo O.; Clark, Timothy (Journal of Physical Chemistry A, 2011)
Unrestricted Natural Orbital–Complete Active Space Configuration Interaction, abbreviated as UNO–CAS, has been implemented for NDDO-based semiempirical molecular-orbital (MO) theory. A computationally more economic technique, UNO–CIS, in which we use a configuration interaction (CI) calculation with only single excitations (CIS) to calculate excited states, has also been implemented and tested. The class of techniques in which unrestricted natural orbitals (UNOs) are used as the reference for CI calculations is denoted UNO–CI. Semiempirical UNO–CI gives good results for the optical band gaps of organic semiconductors such as polyynes and polyacenes, which are promising materials for nanoelectronics. The results of these semiempirical UNO–CI techniques are generally in better agreement with experiment than those obtained with the corresponding conventional semiempirical CI methods and comparable to or better than those obtained with far more computationally expensive methods such as time-dependent density-functional theory. We also show that symmetry breaking in semiempirical UHF calculations is very useful for predicting the diradical character of organic compounds in the singlet spin state.